2015
DOI: 10.1021/acs.organomet.5b00264
|View full text |Cite
|
Sign up to set email alerts
|

Coordination of a Diphosphine–Ketone Ligand to Ni(0), Ni(I), and Ni(II): Reduction-Induced Coordination

Abstract: The coordination chemistry of the diphosphine− ketone ligand 2,2′-bis(diphenylphosphino)benzophenone ( Ph dpbp) with nickel is reported. The ketone moiety does not bind to Ni(II) in the complex ( Ph dpbp)NiCl 2 , whereas reduction to Ni(I) or Ni(0) induces η 2 (C,O) coordination of the ketone to form the pseudotetrahedral complexes ( Ph dpbp)NiCl and ( Ph dpbp)Ni(PPh 3 ). DFT calculations indicate that the metal− ketone bond is dominated by π back-donation; hence, Ph dpbp functions as a hemilabile acceptor lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(47 citation statements)
references
References 37 publications
4
43
0
Order By: Relevance
“…As imilart rend was found for the bands in ATR-IR spectroscopy;t he C=O Figure 1. [15] Both of theset rends suggest that the C=Ob ond is increasingly,a lthough only slightly,w eakened upon the complexation of Ph dpbp to Fe, Co, and Ni. Aco-crystallized toluene molecule and hydrogen atoms are omitted for clarity;ellipsoids are shown at 50 %p robability level.…”
Section: II Cl 2 Complexesmentioning
confidence: 99%
See 3 more Smart Citations
“…As imilart rend was found for the bands in ATR-IR spectroscopy;t he C=O Figure 1. [15] Both of theset rends suggest that the C=Ob ond is increasingly,a lthough only slightly,w eakened upon the complexation of Ph dpbp to Fe, Co, and Ni. Aco-crystallized toluene molecule and hydrogen atoms are omitted for clarity;ellipsoids are shown at 50 %p robability level.…”
Section: II Cl 2 Complexesmentioning
confidence: 99%
“…1 HNMR signals that range from À1.4 to 14.1 and À3.7t o1 8.7 ppm for products 2 and 3,r espectively,i ndicate the formation of paramagnetic complexes. [15] As ystematic comparison of the series of compounds 2-4 provides further insight into the interaction between the un-boundC =Of ragment and the metal. [19] Single-crystal X-ray structure determinations of complexes 2 and 3 revealed that both exhibit ad istorted tetrahedral geometry aroundt he M II centerwithout coordination of the C=Omoiety,which is analogous to the previously reported( Ph dpbp)NiCl 2 complex (4).…”
Section: II Cl 2 Complexesmentioning
confidence: 99%
See 2 more Smart Citations
“…The C−Pd distance (2.176(3) Å) was also lengthened compared to values found in similar complexes . The 13 C NMR shift for the ketone carbon was observed as a broad singlet at 160.4 ppm, significantly upfield from the corresponding value in 2,2′‐bis(diphenylphosphino)benzophenone (196.8 ppm) . Interestingly, the 31 P NMR spectrum exhibits two broad singlets at 39.4 ppm ( Pi Pr 2 ) and −37.2 ppm ( P Me 3 ) instead of the similar AX 2 spin system observed in 2 , 3 , and 4 .…”
Section: Figurementioning
confidence: 71%